Failure of sentinel lymph node mapping in a patient with endometrial cancer with chronic lymphocytic leukemia: A case report. Issue 12 (3rd October 2019) - Vatansever, Dogan; Giray, Burak; Kumcular, Tuncer; Ekemen, Suheyla; Arvas, Macit; Taskiran, Cagatay
Abstract: We aimed to report a detection failure of sentinel lymph node (SLN) mapping via indocyanine green in a patient with endometrial cancer with a previous history of chronic lymphocytic leukemia (CLL), which is a potential risk factor to obstruct lymphatic channels. A 64‐year‐old woman with a 12‐year history of CLL presented to the clinic with grade 2 endometrioid carcinoma. The patient underwent laparoscopic surgical staging. Indocyanine green was used intraoperatively to locate the SLN. No lymph node or lymphatic vessels were identified during SLN mapping. At the final pathology, the morphological findings of CLL were detected in the lymph nodes without metastasis of endometrial cancer. Sentinel lymph node mapping failure due to obstruction of lymphatic channels in a patient with CLL was demonstrated in this study. This is the first report to the best of our knowledge showing SLN mapping failure in the presence of lymphoproliferative diseases.